Retracted: Research Article Flavocoxid Protects Against Cadmium-Induced Disruption of the Blood-Testis Barrier and Improves Testicular Damage and Germ Cell Impairment in Mice. (30th September 2015) - Minutoli, Letteria; Micali, Antonio; Pisani, Antonina; Puzzolo, Domenico; Bitto, Alessandra; Rinaldi, Mariagrazia; Pizzino, Gabriele; Irrera, Natasha; Galfo, Federica; Arena, Salvatore; Pallio, Giovanni; Mecchio, Anna; et al.
Abstract: Cadmium (Cd) causes male infertility. There is the need to identify safe treatments counteracting this toxicity. Flavocoxid is a flavonoid that induces a balanced inhibition of cyclooxygenase (COX)-1 and COX-2 peroxidase moieties and of 5-lipoxygenase (LOX) and has efficacy in the male genitourinary system. We investigated flavocoxid effects on Cd-induced testicular toxicity in mice. Swiss mice were divided into 4 groups: 2 control groups received 0.9% NaCl (vehicle; 1 ml/kg/day) or flavocoxid (20 mg/kg/day ip); 2 groups were challenged with cadmium chloride (CdCl2 ; 2 mg/kg/day ip) and administered with vehicle or flavocoxid. The treatment lasted for 1 or 2 weeks. The testes were processed for biochemical and morphological studies. CdCl2 increased phosphorylated extracellular signal-regulated kinase (p-ERK) 1/2, tumor necrosis factor (TNF)-α, COX-2, 5-LOX, malondialdehyde (MDA), B-cell-lymphoma (Bcl)-2-associated X protein (Bax), follicle-stimulating hormone (FSH), luteinizing hormone (LH), transforming growth factor (TGF) -β3, decreased Bcl-2, testosterone, inhibin-B, occludin, N-Cadherin, induced structural damages in the testis and disrupted the blood-testis barrier. Many TUNEL-positive germ cells and changes in claudin-11, occludin, and N-cadherin localization were present. Flavocoxid administration reduced, in a time-dependent way, p-ERK 1/2, TNF-α, COX-2, 5-LOX, MDA, Bax, FSH, LH, TGF-β3, augmented Bcl-2, testosterone, inhibin B, occludin, N-Cadherin, and improved the structural organization of the testis and the blood-testis barrier. Few TUNEL-positive germ cells were present and a morphological retrieval of the intercellular junctions was observed. In conclusion, flavocoxid has a protective anti-inflammatory, antioxidant, and antiapoptotic function against Cd-induced toxicity in mice testis. We suggest that flavocoxid may play a relevant positive role against environmental levels of Cd, otherwise deleterious to gametogenesis and tubular integrity.